ffect of microstructures on the hydrogen attack to gamma titanium aluminide at low temperature - Hamzah, E.; Suardi, K.; Ourdjini, Ali (http://www.sciencedirect.com/science/journal/09215093, 2005)
EIntermetallic alloys based on gamma titanium aluminide are now regarded as promising candidates for high temperature applications such as for aerospace, marine and automotive engine components, due to their high specific strength and modulus. Their oxidation resistance is good, especially at intermediate and high temperature; oxidation resistance can be obtained up to 800 Â°C. One critical area of application is in combustion engines in aerospace vehicles such as hypersonic airplanes and high-speed civil transport airplanes. This entails the use of hydrogen as a fuel component and it has been widely reported by researchers that these materials exhibit corrosion in the form of environment embrittlement in the presence of hydrogen. A fair amount of research has been carried out to investigate the influence of hydrogen in Î³-titanium aluminide. Some researchers reported that at and lamellar phases had major influence in the susceptible of hydrogen to alloys, while hydrogen is too low to penetrate the Î³-phases. This research focused on the effect of different microstructures of Î³-titanium aluminide to the diffusion coefficient of hydrogen (D) and the corrosion product after hydrogen attack. Modification of Î³-titanium aluminide can be achieved by heat treatment of as-cast binary samples Ti-45% Al and Ti-48% Al. All samples were then subjected to corrosion attack under cathodically charged with galvanostatic mode for 6 h. The potential variation with time was monitored from these data the values of the diffusion coefficient of hydrogen (D) to Î³-titanium aluminide was obtained. D was calculated based on Fick's second Law. These results were compared with that obtained from micro-Vickers hardness profiling, which was measured at cross-section area per depth from the top corroded surface. The hardness values were calculated using the error function equation. An image analyzer; X-ray diffraction (XRD); scanning electron microscope (SEM) and secondary ion mass spectroscopy (SIMS) techniques analyzed hydrides formed at the surface. The results showed that different microstructures have an effect on the diffusion coefficient after hydrogen absorption.